Nasal Leech Retrieval in a German Shepherd Dog: A Case Report - Joshi, Jyotsana Bhatt; Kumar, Pradeep; Gangwar, Chetna; Singh, Alok Kumar; Singh, Renu; Yadav, Jaysanker Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Leeches are hermaphrodite parasites that feed on blood and can vary in length and color. These worms are segmented and have two suckers on them. The term "Hirudiniasis" refers to the infestation caused by this class of leech, which is Hirudinea. The primary habitats of leeches are ponds, lakes, and streams (Abdisa, 2018). The frequency of a nasal leech infestation varies with location. The life cycle begins with the development of eggs encased in cocoons, which then attach themselves to the underwater surface bodies. At last, the juvenile leeches emerge from their cocoons. Dogs and other animals typically get leech infestations when they consume water or swim in rural streams (Chen et al., 2010).
Keywords: eggs; hermaphrodite parasites; leeches